Protocol for measuring force in skinned diaphragm muscle fibers of myopathic SEPN1 knockout mice following chronic tauroursodeoxycholic acid treatment - Leonardo Nogara; Serena Germani; Cosimo De Napoli; Bert Blaauw; Ester Zito (STAR Protocols)
Summary: Selenoprotein N1 (SEPN1) is a type II endoplasmic reticulum (ER) glycoprotein. Loss-of-function mutations in the gene encoding for SEPN1 give rise to myopathy. Here, we present a protocol for evaluating the contractility of diaphragmatic muscle fibers of SEPN1 knockout mice following chronic treatment with tauroursodeoxycholic acid (TUDCA). We describe steps for genotyping SEPN1 knockout mice, TUDCA in vivo treatment, diaphragm dissection, and chemical permeabilization. We then detail procedures for single muscle fiber isolation and tension measurement.For complete details on the use and execution of this protocol, please refer to Germani et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.